AN EXTENSIVE MULTIFACETED EXAMINATION OF EDUCATIONAL DISPARITIES IN SECONDARY SCHOOLS: A COMPREHENSIVE COMPARATIVE STUDY BETWEEN RURALAND URBAN REGIONS IN INDONESIA - Yorman; Heriyanto; Muhammad Abdi Lubis; Ekha Sri Sugiarti; Fitri Astuti Baningtyas (International Journal of Teaching and Learning, 2023)
This comprehensive study extensively explores educational disparities within Indonesian secondary schools, emphasizing a comparative analysis between rural and urban regions. Combining quantitative and qualitative methodologies, we delve into the multifaceted nature of these disparities. Quantitative methods provide us with statistical insights, revealing the extent and significance of the educational disparities. This data, collected through structured surveys, encompasses aspects like access to resources, student performance, and school facilities. Complementing this, qualitative approaches, including in-depth interviews, unearth the lived experiences of students, teachers, and administrators, shedding light on these disparities' social, cultural, and economic dimensions. Our research employs a stratified sampling approach, encompassing the diverse geography of Indonesia, to ensure a representative sample. By random selection within strata, rural and urban schools are well-represented, minimizing bias and yielding generalizable results. Understanding the nuanced challenges of education in varying contexts is essential in a nation as diverse as Indonesia. This study highlights the disparities and offers insights that can inform evidence-based policies, aiming to create more equitable and effective educational systems.